Does Business Culture Enhance Company Performance? Empirical Study of Management Accounting System - Anridho, Nadia; Maulana, Hanif Denta; Rahmatulloh, Sahrian Aditya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to determine the role of management accounting system mediation with organizational culture on company performance. This study used a questionnaire distributed to manufacturing companies registered in the Surabaya Industrial Estate Rungkut and processed using the WarpPLS 6.0 software. The results of this study indicate that organizational culture has a direct positive effect on company performance, and management accounting systems have proven to mediate the influence of business culture on company performance. This study contributes to companies implementing management accounting systems in dealing with environmental uncertainty and improving company performance.